Summer crochet : 19 delicate designs with simple lace and timeless silhouettes - Myska, Janine (Page Street Publishing Co., 2025)
"Transform your summertime wardrobe with fashion-forward, lightweight handmade pieces designed for beach days, vacations and lounging in the sun. Created by designer Janine Myska, who is known for her thorough, size-inclusive patterns and refined, chic sense of style, this collection is the perfect blend of bohemian fashion and summer staples. In addition to clear, detailed instructions, Summer Crochet is chock-full of helpful resources, including comprehensive stitch charts, full sizing charts and plenty of customization tips throughout each pattern, making it easy to personalize this collection and alter each design to fit your unique body type and sense of style. Complete with lace details, open stitchwork and classic silhouettes, Janine's patterns will help you look and feel your best all summer long. You can create the Tropical Beach Dress for a dressed-up vacation dinner, the Boardwalk Bralette for a day by the pool or the Bellflower Bucket Hat to keep the summer sun out of your eyes. Whatever you choose to create, this book provides boutique-quality pieces that will instantly become favorites in your closet. Grab your hook and crochet your way to a sun soaked summer with each of these beautiful, one-of-a-kind designs."--Amazon.